Risk Factors Associated with Maternal and Fetal Complications: A Cross- Sectional Study in the West Bank, Palestine - Al Aqqad, Sana M H; Al Natour, Nihal; Al Tell, Mariam A (International Journal of Human and Health Sciences (IJHHS), 2025)
International Journal of Human and Health Sciences Vol. 09 No. 03 Jul’25 Page: 151-158